Creating web sites : the missing manual - MacDonald, Matthew (O'Reilly, 2005)
Think you have to be a technical wizard to build a great web site? Think again. For anyone who wants to create an engaging web site--for either personal or business purposes--Creating Web Sites: The Missing Manual demystifies the process and provides tools, techniques, and expert guidance for developing a professional and reliable web presence. Like every Missing Manual, you can count on Creating Web Sites: The Missing Manual to be entertaining and insightful and complete with all the vital information, clear-headed advice, and detailed instructions you need to master the task at hand. Author Matthew MacDonald teaches you the fundamentals of creating, maintaining, and updating an effective, attractive, and visitor-friendly web site--from scratch or from an existing site that's a little too simple or flat for your liking. Creating Web Sites: The Missing Manual doesn't only cover how to create a well-designed, appealing, smart web site that is thoroughly up to date and brimming with the latest features. It also covers why it's worth the effort by explaining the rationale for creating a site in the first place and discussing what makes a given web site particularly aesthetic, dynamic, and powerful. It further helps you determine your needs and goals and make well informed design and content decisions. Creating Web Sites: The Missing Manual includes a basic primer on HTML, working with JavaScript, and incorporating services like Paypal's shopping cart, Amazon's associate program, and Google AdSense and AdWords. It delivers advanced tricks for formatting, graphics, audio and video, as well as Flash animation and dynamic content. And you'll learn how to identify and connect with your site's audience through forms, forums, meta tags, and search engines. This isn't just another dry, uninspired book on how to create a web site. Creating Web Sites: The Missing Manual is a witty and intelligent guide for all of you who are ready to make your ideas and vision a web reality.